Children with under-diagnosed asthma presenting to a pediatric emergency department. (13th June 2022) - Pade, Kathryn H.; Thompson, Lindsey R.; Ravandi, Bahareh; Chang, Todd P.; Barry, Frances; Halterman, Jill S.; Szilagyi, Peter G.; Okelo, Sande O.
Abstract: Background: Undiagnosed asthma in children presenting to the emergency department (ED) for respiratory illnesses might be associated with subsequent asthma morbidity and repeat ED visits. Objective: To examine the prevalence of undiagnosed asthma among children presenting for ED care, and explore associations with sociodemographic and clinical characteristics. Methods: We surveyed parents of children ages 2–17 years seeking ED care for respiratory symptoms (including asthma) regarding sociodemographic characteristics, asthma symptoms, prior asthma care and morbidity, and prior asthma diagnosis. Undiagnosed asthma was defined as a positive screening for asthma and no prior diagnosis. We compared sociodemographic and clinical factors of those with diagnosed versus undiagnosed asthma using chi-square, t-tests and multivariable logistic regression model. Results: Of 362 children, 36% had undiagnosed asthma. Undiagnosed children were younger, had younger parents, and had parents less likely to speak English versus diagnosed children (all p < 0.05). Among undiagnosed children, 42% had moderate or severe asthma and 66% reported ≥1 exacerbation in the prior 12 months. Parent-reported controller medication use was higher among diagnosed versus undiagnosed children (60% vs. 21%, p =.001). In a multivariable logistic regression (adjusting for insurance, education, income and preferred language), no controller usage (aOR 4.26), no asthma exacerbations in the prior year (aOR 2.41) and younger age (aOR 0.76) were significantly associated with undiagnosed asthma. Conclusion: Children presenting to the ED with undiagnosed asthma commonly experience significant prior asthma morbidity. Strategies to improve asthma diagnosis and messaging to their parents may reduce future morbidity.